Proposed Marketing Strategy to Increase Service Sales Using the SWOT-Analytic Hierarchy Process Method (Case Study at The Ganteng Barber, Langsa City) - Edi Suwandi; Meri Andriani; Heri Irawan (Fakultas Teknik Universitas Samudra, 2023)
The Handsome Barber is one of the barbershop businesses in Langsa City which was founded by Mr. Musliadi, in 2020 The Handsome Barber was established and had only been running for about 1 year, having its address at Jalan Ahmad Yani. The problems experienced by The Handsome Barber are the ups and downs of the number of customers using The Handsome Barber services every month and the planned targets are not being achieved. The aim of this research is to identify opportunities, threats, strengths, and weaknesses in The Ganteng Barber and create marketing strategies to improve the marketing system. The method used is SWOT and AHP. The results and discussion show that the company's internal and external factors identify strengths, weaknesses, opportunities, and threats with a weighted score of Strengths 0.240, Weaknesses 0.208 Opportunities 0.315, and Threats 0.237. The marketing strategy in improving the marketing system at The Ganteng Barber is the S-O (Strength-Opportunity) Strategy to maintain a quality workforce, the W-O (Weakness-Opportunity) Strategy to maintain quality and good relationships with customers, the S-T (Strength-Threat) Strategy to empower a skilled workforce Experienced and W-T (Weakness-Threat) Strategy Increasing prices must be matched with quality. The conclusion of this study is based on the SWOT analysis Cartesius diagram, The Handsome Barber is in quadrant (I) where the quadrant is a good situation for the company to take advantage of its strengths to exploit existing opportunities.